THE IMPACT OF FINANCIAL TECHNOLOGIES ON THE TRANSFORMATION OF THE FINANCIAL INDUSTRY AND INCREASING ECONOMIC EFFICIENCY (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The process of continuous structural changes in the financial system based on the principles of innovative technologies has a significant impact on the composition and quality of products and services, which is reflected in international practice. The study of the characteristics of financial technologies in the national economy, their impact on the functioning of the global and domestic financial system, the main technological directions and indicators of the financial technology industry market, and the measures and goals developed in Uzbekistan in this regard are among the urgent issues.